The Role of Religiosity, Self-Efficacy, Social Support, and Perceived Organizational Support on The Life Satisfaction of Christian Theological Seminary Lecturers in East Java: Meaning of Work as Mediator - Yusak Novanto; Seger Handoyo; Jenny Lukito Setiawan (Journal of Educational, Health and Community Psychology, 2022)
Achieving life satisfaction is the hope of every person, including lecturers. Based on preliminary study, problem of life satisfaction of PTKK lecturers is a real phenomenon but has never been studied scientifically so far. This study aims to examine the life satisfaction model of PTKK lecturers in terms of religiosity, self-efficacy, social support, and perceived organizational support with the meaning of work as a mediator variable. The research method used in this research is quantitative correlational with participants are 252 lecturers from 41 Christian theological seminaries in East Java. This study uses six instruments to measure each variable and the data analyzed using the SEM-PLS technique. Based on the R2 value for the endogenous variables, it was found that meaning of work got significant positive effect of 36.8% from the independent variables. While the R2 value for the life satisfaction variable is 0.259, which means that life satisfaction can be explained by variance in the independent variables of 25.9%. The results of the research hypothesis indicate that religiosity and self-efficacy have an indirect effect on life satisfaction with the meaning of work as a full mediator, while social support does not affect the meaning of work and life satisfaction. This study also proves that perceived organizational support has a direct and indirect effect on life satisfaction with the meaning of work as a partial mediator. This research result is expected to enhance efforts to increase life satisfaction of lecturers from Christian theological seminaries in East Java.